Análise da competitividade do biocombustível di-amil éter (DAE) para ser utilizado como combustível de aviação - Missaggia, André Brum (2020)
The development of alternative fuels for the aviation sector meets the global need to reduce the emission of greenhouse gases (GHG). This sector alone has generated approximately 2% of global harmful gas emissions, with a projected increase of 3% by 2030 if there are no significant changes (ICAO, 2016; VILT, 2017). In addition, the aviation industry already has ambitious targets for reducing pollutant emissions by 50 to 80%, with the use of biofuels. To this end, the present study aimed to analyze the competitiveness of the di-amyl ether compound (DAE) for use as an additive in the formulation of aviation biofuels. Through the Analytic Hierarchy Process (AHP), the factors that may interfere with the competitiveness of biofuel were prioritized, and with the Fuzzy logic using the input parameters (AHP prioritized criteria) and output (competitiveness), the level of competitiveness was assessed. The methodological approach is characterized by a case study of character combined with information obtained by specialists and by the literature. The results showed that the biofuel di-amyl ether (DAE) has a satisfactory level of competitiveness and has the potential to be incorporated into the Brazilian energy matrix. Costs, Homologation and use and RenovaBio are the most critical criteria for better or worse competitiveness.